Bengt-Ake Lundvall, Hardy Madsen og Jørgen Lindgaard Pedersen (red.), Teknologi mellem økonomi og politik, København: Blytmanns Forlag, 1984, 300 s., 86,00 kr. - Skov Andersen, Arne (Politica, 1985)
-